Natural Evolution of Regurgitation in Children Aged 12-24 Months: A 1-year Cohort Study - Badriul Hegar; Fatima Safra Alatas; Muzal Kadim; Nina Dwi Putri; Wahyu Ika Wardhani (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2013)
Background: There are very limited cohort studies regarding long term outcome of gastroesophageal reflux diseases (GERD), especially until 24 months old. The aim of this study is to see the natural history of GERD in12-24 months old children based on their clinical signs and symptoms.Method: Prospective one year population base cohort study involving 262 children. Their regurgitation history and GERD symptoms were recorded every two months.Results: Two hundred and  fivety three children completed the study. Seventy three children (27.8%) were still having regurgitation when they were 6 months old, 44 (16.7%) until 9 months old, and 24 (9.2%) until 12months old. During 12 months follow-up the prevalence and frequency of regurgitation decreased to 2.4% and 1.2% in the age of 18 and 24 months respectively. Infant with regurgitation at 6 months old were 13.2 times more likely to have regurgitation at 12 months old (RR = 13.2; 95% CI = 4.8-36.6). Prevalence of regurgitation after 18 months old were 37 times higher risk compared to those not regurgitating at the age of 12 months (RR = 37; 95% CI = 2.2–613.9). GERD symptoms were higher in children that were still regurgitating until 9 months old 64.5% (RR = 2.3; 95% CI = 1.7-3.0) compared to those only experiencing until 6 months old 54.7% (RR = 1.3; 95% CI = 1.7-3.0).Conclusion: Regurgitation decrease during 12-24 months old period. The history of regurgitation in 6 and 9 months old is related to the probability to become GERD in 12-24 months old period. Keywords: gastroesophageal reflux, children 12-24 months, GERD symptoms